Pengaruh Manajemen Rantai Pasokan Terhadap Kepuasan Konsumen di PT. Narindo Solusi Telekomunikasi Tab Lotu (Jurnal Riset Manajemen dan Akuntansi, 2025)
This research is motivated by the importance of supply chain management in improving customer satisfaction in telecommunication distribution companies. The main problem addressed is how the implementation of supply chain management, including procurement, distribution, and after-sales services, affects customer satisfaction at PT. Narindo Solusi Komunikasi Tab Lotu. The purpose of this study is to determine the influence of supply chain management on customer satisfaction, both partially and simultaneously. This study employs a quantitative research method with an associative approach. Data were collected through questionnaires distributed to 44 customers of PT. Narindo. The data were analyzed using validity and reliability tests, multiple linear regression, t-test, and coefficient of determination (R²). The findings indicate that supply chain management has a positive and significant effect on customer satisfaction. The t-test results confirm that each dimension of supply chain management partially contributes to customer satisfaction, Moreover, the coefficient of determination (R²) reveals that supply chain management contributes considerably to variations in customer satisfaction, although other external factors also play a role.The conclusion of this research is that the better the implementation of supply chain management at PT. Narindo, the higher the customer satisfaction achieved. Therefore, the company should strengthen aspects such as distribution speed, product availability, and after-sales service quality to continuously improve customer satisfaction